1976
DOI: 10.2466/pr0.1976.39.3f.1199
|View full text |Cite
|
Sign up to set email alerts
|

Educational Orientations of Faculty: Assessing a Personality Model of the Academic Professions

Abstract: This study examined faculty educational orientations and values in the context of Holland's personality and vocational choice model. Faculty ( N = 237) completed the Faculty Orientations Survey and were assigned to a personality group based on Holland's theory. One-way analyses of variance across Holland-type groups generated significant Fs on each subscale. Tukey's HSD a posteriori comparisons yielded significant group differences on various educational “purpose and process” dimensions of the survey, with ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…These studies have examined such wide ranging topics related to the socialization mechanisms of academic environments as the overall departmental and specific classroom teaching goals of faculty (Smart & McLaughlin, 1974;Smart, 1982), the broad educational orientations of faculty and how they interact with their students in in-class and out-of-class settings (Morstain & Smart, 1976), the relative emphasis that faculty place on the development of alternative student competencies in their classes (Smart & Thompson, 2001), and the pedagogical approaches they use in their courses to achieve different student learning outcomes (Peters, 1974;Smart & Umbach, 2007;Smart et al 2009). For example, Morstain and Smart (1976) and Smart and Thompson (2001) found that faculty in Investigative environments placed a greater emphasis on student development of competencies involving mathematical, analytical, and scientific skills and abilities than their colleagues in other academic environments, and tended to have a greater preference for more rational and systematic methods of inquiry.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have examined such wide ranging topics related to the socialization mechanisms of academic environments as the overall departmental and specific classroom teaching goals of faculty (Smart & McLaughlin, 1974;Smart, 1982), the broad educational orientations of faculty and how they interact with their students in in-class and out-of-class settings (Morstain & Smart, 1976), the relative emphasis that faculty place on the development of alternative student competencies in their classes (Smart & Thompson, 2001), and the pedagogical approaches they use in their courses to achieve different student learning outcomes (Peters, 1974;Smart & Umbach, 2007;Smart et al 2009). For example, Morstain and Smart (1976) and Smart and Thompson (2001) found that faculty in Investigative environments placed a greater emphasis on student development of competencies involving mathematical, analytical, and scientific skills and abilities than their colleagues in other academic environments, and tended to have a greater preference for more rational and systematic methods of inquiry.…”
Section: Introductionmentioning
confidence: 99%
“…That is, faculty members are important socializing agents for college students, and through the interactions with departmental faculty, students experience a unique academic sub-environment that may distinctively influence their learning and development. Indeed, the findings of a series of higher education studies (which also employed Holland's work) suggest that the professional attitudes and behaviors of faculty are essential to differential effects of academic disciplines on student development (Morstain and Smart 1976;Smart 1982;Smart and Thompson 2001;Smart and Umbach 2007). For example, Smart and Thompson (2001) found that faculty in Investigative environments encourage students to develop their analytical, mathematical, and scientific abilities more so than their colleagues in other academic environments, while faculty in Artistic environments more strongly encourage students to develop their innovation, creativity, and literary abilities.…”
mentioning
confidence: 99%
“…The other attitude -utilitarian -and generally held by natural scientists -focused on the importance of subject matter. Morstain and Smart (1976) have found similar attitudes and also a link with teaching methods: humanities and social science staff tended to have more desire to share in educational decision-making with students and to favour more individually tailored teaching and learning arrangements. Science and engineering staff tended to be more formal and were characterized by their use of more structured lecture-type teaching.…”
Section: Academic Staff: Some Characteristicsmentioning
confidence: 92%